The Role of Actin Cytoskeleton in Memory Formation in Amygdala - Lamprecht, Raphael (Frontiers in Molecular Neuroscience, 2016)
The central, lateral and basolateral amygdala nuclei are essential for the formation of long-term memories including emotional and drug-related memories. The study of cellular and molecular mechanisms underpinning memory in amygdala may shed light on the formation of memory and on fear and addiction-related disorders. A challenge is to identify molecules activated by learning that subserve cellular changes needed for memory formation and maintenance in amygdala. Recent studies show that activation of synaptic receptors during fear and drug-related learning leads to alteration in actin cytoskeleton dynamics and structure in amygdala. Such changes in actin cytoskeleton in amygdala are essential for fear and drug-related memories formation. Moreover, the actin cytoskeleton subserves, after learning, changes in neuronal morphogenesis and glutamate receptors trafficking in amygdala. These cellular events are involved in fear and drug-related memories formation. Actin polymerization is also needed for the maintenance of drug-associated memories in amygdala. Thus, the actin cytoskeleton is a key mediator between receptor activation during learning and cellular changes subserving long-term memory in amygdala. The actin cytoskeleton may serve as a target for pharmacological treatment of fear memory associated with fear and anxiety disorders and drug addiction to prevent the debilitating consequences of these diseases.